Physical Stability of Commonly Used Medication Administered by Parenteral Nutrition Admixtures in Hospital: A Systematic Review - Erza Genatrika (Journal of Global Pharma Technology, 2020)
Background: Inpatients requiring parenteral nutrition (PN) often need to receive intravenous medication, but physical instability can occur between medications and PN. This review aimed to bring together the available literature on the physical stability of medication with PN used in hospitals. Methods: We conducted a systematic electronic literature search of PubMed, Science Direct, and SpringerLink during the period 2009-2019 for all English language research publications evaluating the physical stability of commonly used medication administered by PN in hospital. Results: Out of 88 studies, 7 studies selected for this review. From all studies conducted in this review found 14 combinations of drugs that are not compatible with PN admixtures, including levetiracetam, albumin, amoxicillin, cefepime, esomeprazole, fluorouracil, pantoprazole, tropics, trace elements, vitamins, and vancomycin. For adding medications directly to the PN solution, specific criteria should be considered, such as physicochemical properties of the ingredients and drug concentration. Conclusion: The stability of IV medications and PN is an important concern in delivering safe and effective medication and nutritional therapy. The role of healthcare professionals is needed to avoid this incident so that patient safety can be guaranteed. Keywords: Parenteral nutrition, Drug, Medication, Stability, Physical.